Matlab simulator for a phased array radar system - Xu, Vincent Jing Wei (2014)
For this project, the author first understands the basic concept of conventional radar and then studies the literature review for phased array radar. Comparison is made between these two radars to understand the advantages and disadvantages. The author has learnt different modules of phased array radar such as antenna patterns about the transmitter and receiver, signal processing, data processing and interface of radar. The author also learns the principles of phased array radar of how each module processes toward the next module. After studying the literature review, the author focuses on the basic functions of Matlab as Matlab will be used as a simulator to construct simulations about phased array radar. It is important for the author to understand most of the basic functions in Matlab in order for the author to produce and understand the results. Different parts of the modules of phased array radar will be simulated. Several codings from books are taken as references to guide along the author for the simulation. In this project, the problems of detecting the signal from a target and tracking of multiples targets have been studied. The author also produces several output interfaces of tracking multiple targets showing their position and range from the radar. Various inputs are set up for different output interfaces. In conclusion, the author uses the literature review and simulation results to visualize how an actual phased array radar functions in practice.